Efek penginjeksian produk intraseluler (icp) dan ekstraseluler (ecp) bakteri Pseudomonas sp. terhadap gambaran darah ikan nila (Oreochromis niloticus): Effect of ECP and ICP Pseudomonas sp. injected to haematology of nile tilapia - Dosim; Esti Handayani Hardi; Agustina (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
This study aimed to determine the effect of Pseudomonas ECP and ICP injection incubated on TSA and TSB media with incubation periad of 72 hours on the nila tilapia (O. niloticus) haematology. Parameters observed were hemoglobin, hematocrit, erythrocyte total and of leukocyte total. The ECP or ICP ware injected into intraperitial nila tilapia as much as 0.2 ml/fish. Observations were made on 6, 12, 24, 48, 72, 96, 120, 144, 168 hour after injection. Extracellular products were obtained by centifuging Pseudomonas suspension grown on TSA and TSB media (incubation time 72 h + 30oC) using a 10.000 g centrifuge for 30 min at 4oC. Supernatant was filtered using filter paper 0.45 μm. To get the ICP, supernatant was centrifuged in room temperature. The results revealed that ICP injection caused the decrease of haematology faster than ECP injection. This indicates that the ICP Pseudomonas more virulent than ECP.